The Effects of Photoperiod Programs on Broiler Chicken Performance and Immune Response - Abbas, Ahmed O.; El-Dein, A.K. Alm; Desoky, A.A.; Galal, Magda A.A. (International Journal of Poultry Science, 2008)
Understanding the role of photoperiod regimens in regulating broiler performance and the immune response is becoming highly important. The objectives of the current investigation are to analyze the effects of photoperiod regimens on humoral and cell-mediated immune response as well as production characteristics in broiler chicken. A total number of 300 one day old male broiler chicks were divided randomly into three equal groups. For 6 weeks, the first group received continuous light (23L:1D) and the second and Third group received non-intermittent restricted light (12L:12D) and intermittent light (2L:2D) respectively. Intermittent light regimen induced activation of both peripheral T and B lymphocyte proliferation and energized antibody production significantly compared to the other two regimens. Furthermore, in the non-intermittent restricted light group, plasma Corticosterone concentration and H/L ratio were significantly higher compared to continuous and intermittent light groups. In addition, intermittent light treatment caused elevation of total white blood cells (WBC) and plasma T3 concentration significantly compared to control. Moreover, intermittent light regimen reduced mortality rate 3 times and improved body weight by 10% compared to control. On the other hand, non-intermittent restricted light regimen had no effect on mortality rate, and suppressed body weight by 10% compared to control. In general, both intermittent and non-intermittent restricted light regimen improved feed conversion significantly compared to continuous light regimen. Even though the intermittent and non-intermittent restricted light regimens have the same period of darkness, the intermittent light regimen would be more beneficial than non-intermittent restricted light program.